Cellular glycosylation senses metabolic changes and modulates cell plasticity during epithelial to mesenchymal transition. Issue 3 (18th August 2017) - Carvalho‐cruz, Patricia; Alisson‐Silva, Frederico; Todeschini, Adriane R.; Dias, Wagner B.
Abstract : Epithelial to mesenchymal transition (EMT) is a developmental program reactivated by tumor cells that leads to the switch from epithelial to mesenchymal phenotype. During EMT, cells are transcriptionally regulated to decrease E‐cadherin expression while expressing mesenchymal markers such as vimentin, fibronectin, and N‐cadherin. Growing body of evidences suggest that cells engaged in EMT undergo a metabolic reprograming process, redirecting glucose flux toward hexosamine biosynthesis pathway (HBP), which fuels aberrant glycosylation patterns that are extensively observed in cancer cells. HBP depends on nutrient availability to produce its end product UDP‐GlcNAc, and for this reason is considered a metabolic sensor pathway. UDP‐GlcNAc is the substrate used for the synthesis of major types of glycosylation, including O ‐GlcNAc and cell surface glycans. In general, the rate limiting enzyme of HBP, GFAT, is overexpressed in many cancer types that present EMT features as well as aberrant glycosylation. Moreover, altered levels of O ‐GlcNAcylation can modulate cell morphology and favor EMT. In this review, we summarize some of the current knowledge that correlates glucose metabolism, aberrant glycosylation and hyper O ‐GlcNAcylation supported by HBP that leads to EMT activation. Developmental Dynamics 247:481–491, 2018 . © 2017 Wiley Periodicals, Inc. Key Findings: Metabolic changes are observed during EMT. Cells engaged in EMT increase the glucose uptake and redirect the flux toward hexosamine biosynthesis pathway which fuels aberrant glycosylation. Increase of O‐GlcNAcylation and GFAT can trigger EMT.